Math Challenges: Making Learning Attractive and Challenging - Siregar, Torang; Amir, Almira (SATKRIYA : Jurnal Pengabdian Kepada Masyarakat, 2023)
The phenomenon of mathematics phobia is a widespread concern within the field of education, which can be attributed to its perceived level of complexity and lack of inherent attractiveness. Nevertheless, the adoption of mathematics is of utmost importance, given its fundamental role in the advancement of scientific and technological disciplines. In order to mitigate concerns, it is imperative to employ pedagogical approaches that are well-organized and captivating. The utilization of mathematical games has been found to be an effective strategy for attracting the attention of kids. This study utilizes a comprehensive analysis of existing literature, focusing on pertinent theoretical sources. Mathematical games play a crucial role as a foundational framework and a valuable tool for research purposes. The study, which was carried out at State High School 1 Sinunukan and the author's place of residence, encompasses the period from the initial semester of 2021 to the final semester of 2023. The results of the study emphasize the potential of utilizing math games as a means to increase students' interest towards the subject. Educators are advised to customize their instructional methods, taking into account the unique abilities of each student, and dedicating much time and effort with compassion and conscientiousness. It is crucial to foster kids' curiosity in mathematics in order to maintain their engagement.